Standard deviation of absorption coefficient spectra of non-algal particles during POLARSTERN cruise PS99 (Version 2) - Liu, Yangyang; Wiegmann, Sonja; Bracher, Astrid (In supplement to: Liu, Yangyang; Boss, Emmanuel; Chase, Alison P; Xi, Hongyan; Zhang, Xiaodong; Röttgers, Rüdiger; Pan, Yanqun; Bracher, Astrid (2019): Retrieval of phytoplankton pigments from underway spectrophotometry in the Fram Strait. Remote Sensing, 11(3), 318, https://doi.org/10.3390/rs11030318, 2025)
Absorption coefficients (abs) and optical density (OD) by total particles, phytoplankton and non-algal particles (NAP) were measured with standard deviation (sd) estimated on water samples collected from underway AC-S flow-through system outflow and CTD. Measurements were performed using QFT-ICAM (Röttgers et al., 2016) as described in Liu et al. (2018) and Liu et al. (2019). 1. About sampling: a) underway samples were collected from unfiltered AC-S outflow (depth: 11m); CTD samples with 5-6 depths were collected on upcast. b) vacuum pressure for filtration: maximum 200 hPa c) samples were measured fresh (not preserved). d) blank filters were collected by soaking them in 0.2um filtered seawater. e) replicates were not collected. 2. About measurements: a) Instrument: light source: UV-VIS lamp (CF-1000- HC lamp, Illumination Technology, USA); absorption meter: Quantitative Filter Technique - Integrating Cavity Absorption Meter (QFT-ICAM) (Röttgers et al., 2016) with 80 mm- diameter integrating sphere; detector: photodiode array spectrometer (AVASPEC-ULS2048-RS-USB2, Avantes, the Netherlands). b) wavelength range of scan and resolution: 313.5-875.7 nm, 0.3 nm. c) slit band width: 2 nm. d) sample filters were bleached with 10% sodium hypochlorite (NaClO) solution for the OD measurement of NAP. e) samples were measured for four times and bleached samples were measured twice. f) dark current and blank filters were measured and subtracted. 3. About data analysis: a) interpolated wavelength range and resolution: 320-844 nm, 2nm. b) wavelength range for fluorescence correction: 670:800 nm. c) diameter of sample patch on GF/F filter: 2.133 cm. d) pathlength amplification factor (beta correction factor): 4.06 (Röttgers et al., 2016). e) no scattering correction for total particle absorption is applied; NAP absorption was adjusted with an offset in the range of 710-750 nm so that the median value of NAP absorption equals the median value of in total particle absorption in this spectral range. This adjustment is based on the assumption that phytoplankton pigments do not absorb in near-infrared (Neeley et al., 2018). This adjustment was not applied to NAP OD data. f) NAP absorption data from underway samples collected during 2016-06-17T21:20, 2016-06-18T00:26, 2016-06-18T03:19, 2016-06-18T06:38, 2016-06-15T12:12, and 2016-06-15T15:09 were missing. To calculate the corresponding phytoplankton absorption, the missing NAP data were taken the same as the ones from 2016-06-17T18:13, 2016-06-18T18:09, 2016-06-18T18:09, 2016-06-18T18:09, 2016-06-15T09:15, and 2016-06-15T09:15, respectively. However, this was not applied to NAP OD data.
Keywords: absorption; non-algal particles; optical density; particulate matter; Phytoplankton